(untitled) (South Asian Journal of Agriculture, 2025)
An experiment was conducted at the net house of Plant Breeding and Biotechnology Laboratory of Agrotechnology Discipline, Khulna University, Bangladesh from March to May, 2019 to study the growth performance of Azolla pinnata in different nutrient media. The experiment was conducted using Completely Randomized Design (CRD) with three replications which consisted of seven treatments namely 20g TSP, 30g TSP, 40g TSP, 50g TSP, 20g TSP + 1 Urea Super Granule, 1 Urea Super Granule and control (fresh water). Each treatment was set in a 35 L bowl where 20 L water and 3 kg soil were added. Data were collected in weekly basis (from 1st to 4th week) for the experiment. No significant variation in plant number was observed at 1st and 2nd week whereas at 4th week, the maximum plant numbers (1629.33) were observed in 50g TSP and the minimum plant numbers (145) were recorded in 1 Urea Super Granule. In case of plant biomass, no significant variation was observed only at 1st week. At 4th week, the maximum plant biomass (43.62g) was observed in 50g TSP and the minimum plant biomass (5.51g) was recorded in 1 Urea Super Granule. The total nitrogen percentage of plant was maximum (9.6%) in 1 Urea Super Granule and the minimum (5.96%) was in 50g TSP. Considering above parameters, growth of Azolla pinnata was found better when it was grown in media containing 50g TSP with 20 L water and 3 kg soil. South Asian J. Agric., Vol. 11, No.1, 2025: 1-7